The Effect of Production Factor Utilization on Rainfed Rice Farming Production: A Case Study in Anggaloosi Village, Onembute District Konawe Regency - Sugiarto, Icuk; Alwi, La Ode; Arif, La Ode Kasno (International Journal of Technology and Education Research, 2025)
This study aims to determine: (1) The effect of production factor utilization on the production of rainfed lowland rice farming in Anggaloosi Village, Onembute District, Konawe Regency; (2) The economic efficiency of production factor use in rainfed lowland rice farming in Anggaloosi Village, Onembute District, Konawe Regency; and (3) The optimal use of production factors in rainfed lowland rice farming in Anggaloosi Village, Onembute District, Konawe Regency. The research was conducted from January to April 2025 in Anggaloosi Village. This study used primary data. The total number of respondents was 43. The analytical methods used were the Cobb-Douglas production function and the marginal product value comparison analysis. The results of the study showed that (1) The factors that had a significant effect on rainfed lowland rice production in Anggaloosi Village, Onembute District, Konawe Regency were land area, urea fertilizer, NPK fertilizer, and pesticides, while seeds and labor had no significant effect on production.(2) The use of production factors in rainfed lowland rice farming in Anggaloosi Village, Onembute District, Konawe Regency has not yet reached an optimal level of economic efficiency—particularly land area, seeds, urea fertilizer, NPK fertilizer, and pesticides—while labor was found to be inefficient.(3) The optimal use of production factors in rainfed lowland rice farming—including land area, seeds, urea fertilizer, NPK fertilizer, pesticides, and labor—still requires further calculation in terms of price and efficiency in order to achieve maximum production